“Why Them, Not Me?”: A Study Exploring The Impact Of Following Fashion Influencers on Instagram on Body Image Satisfaction of Adolescent Girls and Middle-aged Women - Panjrath, Yashvi; Tiwari, Savita (International Journal of Psychosocial Rehabilitation, 2024)
The ongoing interference of social media in our daily lives makes it necessary to explore its impact on mental health. Instagram provides a platform to follow fashion influencers to be updated about fashion trends and tips. These influencers pose a perfect life on social media creating an unrealistic standard for ideal body. Thus, the current study aimed to study whether following fashion influencers on Instagram lead to body image dissatisfaction among Adoloescentgirls and middleaged women. From the data collected it was found that following fashion influencers has been found to have an impact on the followers in various ways, while it can be detrimental for the mental health and well-being of the followers leading to body image dissatisfaction, shrinking of self, it can also have a positive impact on their followers as it is found to develop motivation, inspiration among their followers and help making the followers aware and updated about latest trends